Corallina and Ellisolandia (Corallinales, Rhodophyta) photophysiology over daylight tidal emersion: interactions with irradiance, temperature and carbonate chemistry - Williamson, C. J. (Springer Berlin Heidelberg, 2014)
The photophysiology of three geniculate coralline algal species (Corallina officinalis, C. caespitosa and Ellisolandia elongata) was determined in intertidal rock pools in the south-west UK at Combe Martin (51°12′31N 4°2′19W) and Heybrook Bay (50°31′66N 4°11′41W), at the start, middle and end of summer (September 1 and 2) and winter (February 9 and 10) daylight tidal emersion periods, in relation to prevailing irradiance, temperature and carbonate chemistry conditions. Algal photophysiology was assessed from rapid light curves performed using pulse amplitude modulation fluorometry. Corallina and Ellisolandia experienced significant fluctuations in irradiance, temperature and carbonate chemistry over seasonal and tidal cycles. Rock pool carbonate chemistry was predictable (R (2) = 0.82, P < 0.0001) by photodose (summed irradiance) plus water temperature, but not significantly related to photophysiology. In contrast, Corallina and Ellisolandia relative maximum electron transfer rate showed a significant negative relationship (R (2) = 0.65, P < 0.0001) with irradiance plus water temperature. At a seasonal resolution, photoacclimation to maximize both light harvesting during winter months and photoprotection during summer months was observed for all species. Dynamic photoinhibition was apparent over both summer and winter tidal emersion, in relation to irradiance fluctuations. More effective photoinhibition was apparent during summer months, with greater sensitivity to irradiance and slower recovery in F (v)/F (m), observed during winter. With sustained high irradiance over tidal emersion, the establishment of high pH/low inorganic carbon conditions may impact photochemistry. This study represents the first assessment of C. officinalis, C. caespitosa and E. elongata photophysiology underpinned by clear species concepts and highlights their ability to adapt to the dramatically fluctuating conditions experienced in intertidal rock pools.